Report of the Task Force on Grasslands and Desserts - Planning Commission (Planning Commission Government of India, 2007)
The Report of the Task Force on Grasslands and Deserts underscores the urgent need for dedicated policies and programs to conserve India’s grassland and desert ecosystems, which are vital for biodiversity, livestock fodder, and rural livelihoods. Key threats include overgrazing, land conversion, and insufficient legal protection. The report recommends establishing a National Grazing Policy, enhancing Protected Areas, implementing flagship species projects like Project Bustard and Project Snow Leopard, and initiating long-term ecological research. It emphasizes community engagement, cross-ministerial collaboration, and the integration of grassland and desert conservation into national development policies to achieve sustainable ecosystem management and socio-economic benefits.
Government of India Planning Commission New Delhi
Keywords: Grasslands; Deserts; Biodiversity Conservation; Livestock Management; National Grazing Policy; Flagship Species; Protected Areas; Environmental Impact Assessment; Ecological Research; Climate Change